Psychosocial factors of psychological maladaptation in female patients of a cosmetology clinic - E. S. Bagnenko (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. In the field of aesthetic medicine, there is a lack of psychological research despite the obvious impact of cosmetic defects on the emotional state and social functioning of a person. Only a few studies indicate psychological maladaptation in patients of a cosmetology clinic, which is reflected in the frequency of the occurrence of anxiety, depression and personality disorders exceeding their levels in population. The objective was to identify psychosocial factors associated with the risk of psychological maladaptation in female patients of the cosmetology clinic. Methods and materials. To achieve the goal, female patients (n=161, mean age was 39.53±0.86 years) were studied using the author’s structured interview and 7 psychodiagnostic methods: «Neuropsychic Adaptation Test» (NPA), «Social Frustration Level» (SFL), «Visual Analogue Self-Esteem Scale» (VASES), «Semantic Time Differential» (STD), «Perceived Stress Scale» (PSS-10), «Well-Being Index» (WHO-5), «Quality of Life Satisfaction Questionnaire» (QOL). Groups of female patients without psychological maladaptation (group 1, n=74) and those with psychological maladaptation (group 2, n=87), selected on the basis of the final NPA test score were compared. Results. The results showed a statistically significant predominance in group 2 compared to group 1 of the frequency of emotionally neutral relationships with their own children, of living alone, as well as dissatisfaction in significant areas of life, especially in the material economic sphere, in the sphere of self-accepting as a personality and one’s physical «Ego», in the sphere of attitude to past and present life. In group 2, higher rates of perceived stress and frequency of psychotraumatic situations in anamnesis as well as lower rates of general psychological well-being and satisfaction with the quality of life were revealed. Conclusion. The factors influencing the psychological maladaptation in female patients of the cosmetology clinic were identified. The prospects of the study associated with the determination of the most informative factors for the prognosis of psychological adaptation based on the analysis on not only psychological but also individual and personal characteristics in female patients of the cosmetology clinic were indicated.